Determinants of Covid-19 Vaccine Uptake Amongst Traders in Wakulima Market, Nairobi City County, Kenya - Opande, Collins Ochieng (Amref International University, 2025)
Background: This research focuses on determining factors that influence the uptake of the COVID-19 vaccine among traders in Nairobi's Wakulima Market, Kenya. The investigation centers on understanding how contextual, individual, and perceptual elements impact their decisions to receive the vaccine. Broad Objective: To assess the contextual, individual, and perceptual components influencing the COVID-19 vaccine uptake among traders in Wakulima Market. Methods: The research was underpinned by theoretical frameworks, including the Theory of Planned Behaviour, Social Cognitive Theory, and the Health Belief Model. Adopting a mixed-methods approach, the study encompassed a demographic of 3,000 traders in Wakulima Market, selecting 353 participants through simple random sampling. Data collection involved the use of questionnaires and interviews. Upon collection, the data underwent a thorough check for completeness, followed by coding and input into SPSS version 25.0. The study’s data comprised both quantitative and qualitative aspects, analyzed using descriptive statistical methods like percentages, frequencies, and tables, in addition to correlation and regression analysis to explore relationships among the variables. The qualitative data was examined thematically in alignment with the objectives of the study. Findings: The study found and concluded that taking all factors (perceptual factors, individual factors, and contextual factors) to be constant at zero, COVID-19 vaccine uptake amongst traders would be 2.938. Also, with the three variables, a unit rise in contextual factors would lead to a .143 rise in the COVID-19 vaccine uptake amongst traders indicating significant influence (p=.004) and a unit rise in individual factors led to a .135 increase in the COVID-19 vaccine uptake amongst traders indicating significant influence (p=.005) while a unit increase in perceptual factors led to a .149 increase in the COVID-19 vaccine uptake amongst traders indicating significant influence (p=.002). Conclusions and Recommendations: The study concluded that contextual, individual, and perceptual elements significantly impacted COVID-19 vaccine uptake among traders. It recommends that the Ministry of Health conduct on-site Vaccination Drives where on-site vaccination drives within Wakulima Market should be organized, where traders receive the vaccine without having to leave their businesses. The study further recommends tailored messaging targeting traders which should emphasize how vaccination protects traders' livelihoods and the market's economic stability. Finally, the study recommends the implementation of a peer-to-peer engagement strategy by recruiting and training a group of vaccinated traders to act as peer advocates. Peer-to-peer interactions will be effective in building trust and overcoming resistance.
A Research Thesis Submitted to The Department of Community Health, School of Public Health, In Partial Fulfillment For the Requirement for The Award of Master of Public Health (Applied Epidemiology) of Amref International University
Keywords: Covid-19 Vaccine Uptake